Preventing money laundering : a legal study on the effectiveness of supervision in the European Union - Broek, Melissa van den (Eleven International Publishing, 2015)
Money laundering is criminalized virtually all around the world and has been a law enforcement priority since the early 1990s. The international nature of money laundering, combined with estimations on the scope and the distorting effects it may bring about, makes it a grave danger to national and international financial markets. At the same time, money laundering is considered to be a danger to society due to its strong interaction with organized drugs and white-collar crime. Over the years, a 'twin-track approach' has been developed, aimed at the prevention of money laundering on the one han.